Exploring Gen-Z Learning Preferences: A Comparative Study of Traditional, Online, and Blended Learning Models - Princes, Elfindah; Soeryanto, Novianti; Romprasert, Suppanunta (APPS Publications, 2024)
Purposes - The primary objectives of this research are to explore Gen-Z’s preferred learning environments, identify the factors influencing their choices, and uncover the challenges and opportunities associated with each learning model. Additionally, the study aims to provide actionable insights for educational policy-making and practice. Methodology - A quantitative research approach was employed, utilizing surveys distributed to a diverse sample of Gen-Z students aged 18-24 currently enrolled in higher education. The survey collected data on participants' preferences, engagement levels, and the effectiveness of different learning models. Statistical analyses were performed to assess the relationships between the variables. Findings - The findings reveal that Gen-Z shows a strong preference for online and blended learning models over traditional classroom settings. The study highlights the significant impact of elements such as connectivism and constructivism on learning model effectiveness, while factors like student engagement and participant information also play moderate roles. However, the direct influence of knowledge acquisition on the choice of learning model was found to be minimal. Novelty - This research contributes to the limited academic literature on Gen-Z learning preferences by focusing on the comparative effectiveness of different educational models. The study provides a contemporary understanding of how digital natives interact with learning environments, offering insights that are crucial for developing future educational strategies. Research Implications - The study’s results have practical implications for educators and policymakers. By aligning teaching methods with Gen-Z’s preferences, educational institutions can enhance student engagement and learning outcomes. Furthermore, the research underscores the need for integrating technology into education and preparing for future shifts in learning trends among younger generations.